2023
DOI: 10.3390/futurepharmacol3020025
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant Effect of Alpha Lipoic Acid in Rats Exposed to Chronic Unpredictable Mild Stress: Putative Role of Neurotransmitters and 5HT3 Receptor

Abstract: Depression is a neuropsychiatric disorder characterized by altered emotion and cognition. Alpha lipoic acid (ALA) is a potent natural antioxidant and exhibits neuroprotective effects. However, its antidepressant activity and its mechanism of action in rats exposed to chronic unpredictable mild stress (CUMS) need to be evaluated. The rats were divided into six groups. Group, I vehicle control (without stress), II- CUMS, III- fluoxetine (FLX) (50 mg/kg p.o.), IV, V, and VI were treated with ALA (50, 100, 200 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…The docking study also revealed that ALA has a potent antagonistic effect on 5-HT 3 R, perhaps mitigating symptoms of depression. Furthermore, the fact that ALA’s nutraceutical qualities prevent stress-induced depression-like behavior is also highlighted …”
Section: Depressionmentioning
confidence: 97%
See 1 more Smart Citation
“…The docking study also revealed that ALA has a potent antagonistic effect on 5-HT 3 R, perhaps mitigating symptoms of depression. Furthermore, the fact that ALA’s nutraceutical qualities prevent stress-induced depression-like behavior is also highlighted …”
Section: Depressionmentioning
confidence: 97%
“…Furthermore, the fact that ALA's nutraceutical qualities prevent stress-induced depression-like behavior is also highlighted. 87 Fructus Aurantii (FA) is the dried immature fruit of Citrus aurantium L. (Rutaceae). It contains multiple phytoconstituents that have neuroprotective effects.…”
Section: ■ Depressionmentioning
confidence: 99%